2000
DOI: 10.1182/blood.v96.3.1030
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-independent commitment phase to apoptosis in activated blood T lymphocytes: reversibility at low apoptotic insult

Abstract: Little is known about the mechanisms of programmed death triggered in T lymphocytes by stimuli that can bypass caspase activation. Anti-CD2 monoclonal antibody and staurosporine are such apoptosis inducers because they operate in the presence of broad-spectrum caspase inhibitors BOC-D.fmk and Z-VAD.fmk. A system was devised, based on the isolation according to density of activated blood T cells progressively engaged in the apoptotic process. This allowed definition of a sequence of caspase-dependent and caspas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(10 citation statements)
references
References 49 publications
2
7
1
Order By: Relevance
“…Recent publications have proposed that apoptosis would follow a general scheme where cytochrome c release from mitochondria would stimulate the activation of caspases, which then triggers AIF release from mitochondria 45 . Our data are in agreement with other studies that have described the release of AIF in the absence of detectable caspase activation 20,46 …”
Section: Discussionsupporting
confidence: 91%
“…Recent publications have proposed that apoptosis would follow a general scheme where cytochrome c release from mitochondria would stimulate the activation of caspases, which then triggers AIF release from mitochondria 45 . Our data are in agreement with other studies that have described the release of AIF in the absence of detectable caspase activation 20,46 …”
Section: Discussionsupporting
confidence: 91%
“…It is possible that ZVAD‐FMK might not be sufficient to inhibit apoptotic signalling from mitochondria in TDH‐exposed Rat‐1 cells. Alternatively, recent evidence from an increasing number of experimental systems using ZVAD‐FMK supports the notion that apoptosis can also proceed in a caspase‐independent manner [26,27]. This pathway is another possibility of TDH action leading to apoptosis.…”
Section: Discussionmentioning
confidence: 89%
“…These data suggest that in hypoxic conditions, unlike ischemic insult, apoptotic processes are aborted despite a high neuronal level of caspase‐3 cleaved product as shown by immunostaining experiments. Some recent in vitro studies reported that apoptogenic events such as the cytochrome c release, the initial collapse of mitochondrial inner transmembrane potential, as well as the mitochondrial release of apoptosis‐inducing factor were reversible depending on the strength of the stimulus (Dumont et al ., 2000). In primary rat hippocampal neurons, membrane phosphatidylserine exposure, a marker of apoptosis, was shown to be reversible in the initial 6‐h period following NO toxic injury (Lin et al ., 2000).…”
Section: Discussionmentioning
confidence: 99%